PEDAGANG WARUNG AMPERA MALAM DI KOTA PEKANBARU (Studi Kasus di Kecamatan Tampan) - Nanda Silvia Andriani; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at Jl. H. R. Soebrantas, Kecamatan Tampan, Pekanbaru City with the aim to find out the socio-economic life of AMPERA stall traders and to find out the involvement of family worker as well as the family workers wage distribution of AMPERA night stall traders. This research uses descriptive qualitative research methods. The subjects in this study amounted to 4 people as informants and the selection of the informants was carried out using purposive sampling techniques which means determining the informants based on certain considerations. Researcher was looking for subjects who have been selling and become the owners of AMPERA night stalls for more than 5 years and above and the subjects that the researchers took are also the informants who were willing to be interviewed. In collecting data, researchers used the observation techniques, in-depth interviews and documentation. This study uses the theory of rational choice by James Coleman, that the existence of an individual action leads to a goal and that goal is an action which is determined by norms and values and preferences (choices). In running a business, it is necessary to have actors and supporting resources. The owner of AMPERA night stall which is the main actor of this economic activity also needs other supporting resources which are usually called workers/labors. The results of the descriptive analysis showed that the socio-economic living conditions of the AMPERA night stall traders along Jl. H.R. Soebrantas, Tampan District, Pekanbaru City has the level of education that disable them to be in the formal sector, so they try to open their own businesses even though these businesses are only categorized as small-scaled businesses. The involvement of family workers or close relatives in the informal sectoris quite common even though the employees/laborers who assist in running the business are family to the owners or are having close family relations, they certainly do not escape the desire to get paid even though not as much.Key Words : Socio-Economic, Family Workers, AMPERA Stall Traders.